Letter to the American Church - Metaxas, Eric (Salem Books, 2022)
"In an earnest and searing wake-up call, the author of the bestseller Bonhoeffer: Pastor, Martyr, Prophet, Spy warns of the haunting similarities between today's American church and the German church of the 1930s. Echoing Bonhoeffer's prophetic call, Eric Metaxas exhorts his fellow Christians to repent of their silence in the face of evil before it is too late."Silence in the face of evil is itself evil. Not to speak is to speak. Not to act is to act. God will not hold us guiltless."Turning the other cheek does not mean standing by while the enemies of God dismantle Christian civilization and brainwash our children. Decrying the cowardice that masquerades as meekness, Eric Metaxas summons the Church to battle.An attenuated and unbiblical "faith" based on what Bonhoeffer called "cheap grace" has sapped the spiritual vitality of millions of Americans. Paying lip service to an insipid "evangelism," they shrink from combating the evils of our time. Metaxas refutes the pernicious lie that fighting evil politicizes Christianity. As Bonhoeffer and other heroes of the faith insisted, the Church has an irreplaceable role in the culture of a nation. It is our duty to fight the powers of darkness, especially on behalf of the weak and vulnerable.Silence is not an option. God calls us to defend the unborn, to confront the lies of cultural Marxism, and to battle the globalist tyranny that crushes human freedom. Confident that this is His fight, the Church must overcome fear and enter the fray, armed with the spiritual weapons of prayer, self-sacrifice, and love."--publisher.